2017
DOI: 10.1016/j.metabol.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D replacement in children, adolescents and pregnant women in the Middle East and North Africa

Abstract: Introduction Hypovitaminosis D affects one-third to two-thirds of children and pregnant women from the Middle East and North Africa (MENA) region. Objective To evaluate in infants, children, adolescents and pregnant women, from the MENA region, the effect of supplementation with different vitamin D doses on the change in 25-hydroxyvitamin D [25(OH)D] level reached, and other skeletal and non-skeletal outcomes. Methods This is a systematic review of randomized controlled trials of vitamin D supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 44 publications
(135 reference statements)
6
31
0
Order By: Relevance
“…low-income settings in India, Bangladesh, Indonesia, Tanzania, Gambia, Zimbabwe, Kenya, Ghana, Peru, and Brazil (Oliveira et al [ 21 ]) Pregnant and puerperal women (Neves et al [ 20 ]) Lactating women (Caminha et al [ 19 ]) Pregnant women (Thorne-Lyman and Fawzi [ 25 ]; McCauley et al [ 24 ]) Pregnant women (Christesen et al [ 22 ]; De-Regil et al [ 17 ]; Roth et al [ 9 ]) Adult women of age > 18 years (Reid et al [ 27 ]) Pregnant women, children, and adolescents (Chakhtoura et al [ 26 ]) Children, adolescents, pre-pregnant women, women of reproductive age group, and post-menopausal women (Das et al [ 28 ]) Adult women of age > 18 years (Trowman et al [ 29 ]; Cumming [ 30 ]) Pregnant women (Buppasiri et al [ 31 ]). Obese/ overweight participants (Onakpoya et al [ 32 ]) Pregnant and puerperal women (Arthur et al [ 18 ]) Pre-pregnant women, women of reproductive age group, and post-menopausal women (Das et al [ 28 ]) included Intervention Supplementation of vitamin A alone or in combination with other micronutrients (Oliveira et al [ 21 ]; McCauley et al [ 24 ]; Neves et al [ 20 ]) Supplementation of vitamin A/beta carotene (Thorne-Lyman and Fawzi [ 25 ]; Caminha et al [ 19 ]) Supplementation of vitamin D (Chakhtoura et al [ 26 ]; Christesen et al [ 22 ]; Reid et al [ 27 ]; De-Regil et al [ 17 ]; Roth et al [ 9 ]) Fortified food with vitamin D along with other micronutrients (Das et al [ 28 ]) Calcium supplementation with or without dairy products or combined calcium supplementation (Trowman et al [ 29 ]; Cumming [31]; Buppasiri et al [ 31 ]; Onakpoya et al [ 32 ]; Arthur et al [ 18 ]) Alkaline phosphatase and s...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…low-income settings in India, Bangladesh, Indonesia, Tanzania, Gambia, Zimbabwe, Kenya, Ghana, Peru, and Brazil (Oliveira et al [ 21 ]) Pregnant and puerperal women (Neves et al [ 20 ]) Lactating women (Caminha et al [ 19 ]) Pregnant women (Thorne-Lyman and Fawzi [ 25 ]; McCauley et al [ 24 ]) Pregnant women (Christesen et al [ 22 ]; De-Regil et al [ 17 ]; Roth et al [ 9 ]) Adult women of age > 18 years (Reid et al [ 27 ]) Pregnant women, children, and adolescents (Chakhtoura et al [ 26 ]) Children, adolescents, pre-pregnant women, women of reproductive age group, and post-menopausal women (Das et al [ 28 ]) Adult women of age > 18 years (Trowman et al [ 29 ]; Cumming [ 30 ]) Pregnant women (Buppasiri et al [ 31 ]). Obese/ overweight participants (Onakpoya et al [ 32 ]) Pregnant and puerperal women (Arthur et al [ 18 ]) Pre-pregnant women, women of reproductive age group, and post-menopausal women (Das et al [ 28 ]) included Intervention Supplementation of vitamin A alone or in combination with other micronutrients (Oliveira et al [ 21 ]; McCauley et al [ 24 ]; Neves et al [ 20 ]) Supplementation of vitamin A/beta carotene (Thorne-Lyman and Fawzi [ 25 ]; Caminha et al [ 19 ]) Supplementation of vitamin D (Chakhtoura et al [ 26 ]; Christesen et al [ 22 ]; Reid et al [ 27 ]; De-Regil et al [ 17 ]; Roth et al [ 9 ]) Fortified food with vitamin D along with other micronutrients (Das et al [ 28 ]) Calcium supplementation with or without dairy products or combined calcium supplementation (Trowman et al [ 29 ]; Cumming [31]; Buppasiri et al [ 31 ]; Onakpoya et al [ 32 ]; Arthur et al [ 18 ]) Alkaline phosphatase and s...…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation of vitamin D (Chakhtoura et al [ 26 ]; Christesen et al [ 22 ]; Reid et al [ 27 ]; De-Regil et al [ 17 ]; Roth et al [ 9 ])…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was consistent with what was reported by Rajakumar et al (35) who showed that 2098 IU of vitamin D/d were needed to maintain serum 25(OH)D levels at 50 nmol/l in 97•5 % of US children. A systematic review and meta-analysis from Middle East and North Africa (NENA region) also suggested that a daily dose of 1000-2000 IU of vitamin D will be required to obtain serum 25(OH)D levels of >50 nmol/l in the majority of the paediatric population (27) . These observations raise doubts about the adequacy of current recommendations of 400 IU/d by ICMR or 600 IU/d by IAP and IOM for Indian children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cooper et al 39 found supplementation of women with cholecalciferol 1000IU/day during pregnancy is safe and sufficient to ensure repletion of VD stores in pregnant women and Yilmaz et al 40 documented that VD-ST with 1200IU/day from the 12 th GW can prevent neonatal VD deficiency. Also, Chakhtoura et al 41 reported that in pregnant women VD dose of 1000-2000IU daily may be necessary to allow for the majority of this population to have serum VD level of 50nmol/L.…”
Section: Discussionmentioning
confidence: 99%